Calendering‐Compatible Macroporous Architecture for Silicon–Graphite Composite toward High‐Energy Lithium‐Ion Batteries. Issue 37 (2nd August 2020) - Son, Yeonguk; Kim, Namhyung; Lee, Taeyong; Lee, Yoonkwang; Ma, Jiyoung; Chae, Sujong; Sung, Jaekyung; Cha, Hyungyeon; Yoo, Youngshin; Cho, Jaephil
Abstract: Porous strategies based on nanoengineering successfully mitigate several problems related to volume expansion of alloying anodes. However, practical application of porous alloying anodes is challenging because of limitations such as calendering incompatibility, low mass loading, and excessive usage of nonactive materials, all of which cause a lower volumetric energy density in comparison with conventional graphite anodes. In particular, during calendering, porous structures in alloying‐based composites easily collapse under high pressure, attenuating the porous characteristics. Herein, this work proposes a calendering‐compatible macroporous architecture for a Si–graphite anode to maximize the volumetric energy density. The anode is composed of an elastic outermost carbon covering, a nonfilling porous structure, and a graphite core. Owing to the lubricative properties of the elastic carbon covering, the macroporous structure coated by the brittle Si nanolayer can withstand high pressure and maintain its porous architecture during electrode calendering. Scalable methods using mechanical agitation and chemical vapor deposition are adopted. The as‐prepared composite exhibits excellent electrochemical stability of > 3.6 mAh cm −2, with mitigated electrode expansion. Furthermore, full‐cell evaluation shows that the composite achieves higher energy density (932 Wh L −1 ) and higher specific energy (333 Wh kg −1 ) with stable cycling than has been reported in previous studies. Abstract : There is a gap between lithium‐ion batteries in academia and industry, which is the lack of consideration of industrial requirements in terms of electrode conditions, such as calendering. In this work, a calendering‐compatible macroporous design is presented. This unique design enables both high electrode density without any collapse of pores and an excellent energy density with good cycle life under practical conditions.